Multimodal Management of Upper and Lower Extremity Lymphedema - Schaverien, Mark V.; Dayan, Joseph H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
In this concise, accessible, and comprehensive reference, world experts in the field of lymphedema detail all of the non-surgical and surgical approaches to the multidisciplinary management of patients with upper and lower extremity lymphedema. There is particular focus on the surgical treatments for lymphedema, where the reader is taken step-by-step through illustrated guides for each procedure by the leading experts in the field of lymphedema microsurgery; from patient selection, preoperative evaluation, surgical technique, and postoperative management. The book is strictly organized so that readers can quickly find content and provides readers with the necessary tools and framework to readily apply these innovative and state-of-the art techniques to their patients to optimize outcomes of surgical and non-surgical treatments for their lymphedema patients. Each chapter features a standardized content layout with full-color illustrations and clinical photographs to visually represent the content and includes key tips from experts in lymphedema, accompanied by key video contributions from the authors to demonstrate the surgical techniques. There is key emphasis on advances in our understand of the etiology of lymphedema, the most important surgical topics in lymphedema microsurgery, the current evidence available for the surgical treatment of lymphedema, and recent advances in lymphedema including new pharmacological treatments that target inflammation and fibrosis Edited by leaders in lymphedema microsurgery and contributed to by a multidisciplinary group of international experts to provide a full and comprehensive guide, Multimodal Management of Upper and Lower Extremity Lymphedema is aimed at a wide target audience that includes surgeons that perform lymphedema surgeries, other medical specialties that treat patients with cancer, lymphedema therapists, physical therapists, and occupational therapists, as well as nursing specialties and trainees.
Introduction -- Anatomy of the Lymphatic System -- Pathophysiology and Molecular Research in Lymphedema -- Lymphedma Prospective Surveillance and Risk Reduction -- Multimodal Evaluation of the Lymphedema Patient -- Non-Surgical Management of the Lymphedema Patient -- Patient-Selection and Evidence-Based Algorithmic Approach to Surgical Management of Lymphedema -- Instruction: Lymphaticovenular Anastomosis (LVA) Assessment and Planning -- Step-by-step instruction: Single Site Multiple Lymphatic Venous Anastomosis Technique -- Step-by-step Instruction: Superficial Inguinal (groin) vascularized Lymph -- Combined Microvascular Breast Reconstruction and Groin Vascularized Lymph Node Transplant Procedure -- Step-by-Step Instruction: Submental Vascularized Lymph Node Transplant Procedure -- Step-by-step Instruction: Supraclavicular vascularized Lymph node Transplant Procedure -- Step-by-Step Instruction: Lateral Thoracic Vascularized Lymph Node Transplant Procedure -- Step-by-Step Instruction: Omental Vascularized Lymph Node Transplant Procedure: Laparoscopic and Open Harvest Techniques -- Step-by-Step Instruction: Jejunal Mesenteric Vascularized lymph node transplant procedure -- Step-by-Step Instruction: Suction-Assisted Lipectomy Procedure with Controlled Compression Therapy -- Vascularized Lymph Node Transplant and Recipient Site Selection -- Step-by-Step Instruction: Suction-Assisted Protein Lipectomy Procedure Combined with Vascularized Lymph Node Transfer -- Step-by-Step Instruction: Direct Excision Combined with Lymphatic Microsurgery -- Step-by-Step Instruction: Immediate Lymphatic Reconstruction for Lymphedema Risk Reduction in Breast Cancer Management -- Key Topic: Evidence-Based Outcomes of Lymphedema Microsurgery -- Evaluating Outcomes of Lymphedema Surgery -- New and Emerging Therapies for Lymphedema: Part I -- New and Emerging Therapies for Lymphedema: Part II -- Lymphatic Education & Research Network Centers of Excellence: A Multidisciplinary Approach to Lymphatic Care.
Keywords: Surgery; Internal medicine; Surgery; Internal Medicine; Lymphedema -- diagnosis; Lymphedema -- therapy; Upper Extremity; Lower Extremity